PML protein organizes heterochromatin domains where it regulates histone H3.3 deposition by ATRX/DAXX - Delbarre, Erwan; Ivanauskiene, Kristina; Spirkoski, Jane; Shah, Akshay; Vekterud, Kristin; Moskaug, Jan Øivind; Bøe, Stig Ove; Wong, Lee H.; Küntziger, Thomas; Collas, Philippe (Genome Research, 2017)
Maintenance of chromatin homeostasis involves proper delivery of histone variants to the genome. The interplay between different chaperones regulating the supply of histone variants to distinct chromatin domains remains largely undeciphered. We report a role of promyelocytic leukemia (PML) protein in the routing of histone variant H3.3 to chromatin and in the organization of megabase-size heterochromatic PML-associated domains that we call PADs. Loss of PML alters the heterochromatic state of PADs by shifting the histone H3 methylation balance from K9me3 to K27me3. Loss of PML impairs deposition of H3.3 by ATRX and DAXX in PADs but preserves the H3.3 loading function of HIRA in these regions. Our results unveil an unappreciated role of PML in the large-scale organization of chromatin and demonstrate a PML-dependent role of ATRX/DAXX in the deposition of H3.3 in PADs. Our data suggest that H3.3 loading by HIRA and ATRX-dependent H3K27 trimethylation constitute mechanisms ensuring maintenance of heterochromatin when the integrity of these domains is compromised.